2018
DOI: 10.1002/ange.201804072
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Aliphatic Phosphines by Auxiliary Phosphine Sulfides Offers Zeptomolar Affinity and Unprecedented Selectivity for Probing Biological CuI

Abstract: Full elucidation of the functions and homeostatic pathways of biological copper requires tools that can selectively recognize and manipulate this trace nutrient within living cells and tissues, where it exists primarily as CuI. Buffered at attomolar concentrations, intracellular CuI is, however, not readily accessible to commonly employed amine and thioether‐based chelators. Herein, we reveal a chelator design strategy in which phosphine sulfides aid in CuI coordination while simultaneously stabilizing aliphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To corroborate these findings, we used the recently developed ratiometric Cu(I)-selective fluorescent probe, crisp-17, as another readout for bioavailable Cu 25 . The probe was first validated using the cell-permeant complex CuGTSM (glyoxalbis(N 4 -methyl-3-thiosemicarbazonato) copper(II)) and a Cu(I)-specific chelator (PSP-2) 29 , which confirmed that the probe reversibly responds to changes in cellular Cu levels ( Supplementary Fig. 5e, f).…”
Section: Kras G12vmentioning
confidence: 77%
“…To corroborate these findings, we used the recently developed ratiometric Cu(I)-selective fluorescent probe, crisp-17, as another readout for bioavailable Cu 25 . The probe was first validated using the cell-permeant complex CuGTSM (glyoxalbis(N 4 -methyl-3-thiosemicarbazonato) copper(II)) and a Cu(I)-specific chelator (PSP-2) 29 , which confirmed that the probe reversibly responds to changes in cellular Cu levels ( Supplementary Fig. 5e, f).…”
Section: Kras G12vmentioning
confidence: 77%
“…4−6 While dissociation constants below 1 fM are challenging to realize with commonly employed synthetic Cu(I) chelators based on thioether donors, 7−9 we recently demonstrated that dissociation constants down to 10 zM are attainable with aliphatic phosphine-based ligands containing auxiliary phosphine sulfide moieties. 10 The latter not only participate in Cu(I) coordination but also exert an electron-withdrawing effect on the phosphine sites, thus stabilizing the free ligand against protonation and oxidation. These phosphine sulfide-stabilized phosphines, typified by PSP-1 and PSP-2 (Chart 1), maintain strong Cu(I) coordinating ability despite dramatically reduced basicity compared to typical aliphatic phosphines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With a 1:1 Cu(I) complex stability constant of log K = 20.0 (K d = 10 zM), PSP-2 offers an unprecedented Cu(I) affinity among synthetic ligands and is unaffected by Mn(II), Fe(II), or Zn(II), even at millimolar concentrations. 10 The Cu(I) complexes of both PSP-1 and PSP-2, however, engage in additional dimerization equilibria at high micromolar concentrations, hampering the utility of these ligands for applications where Cu(I) availability must be precisely controlled. We previously obtained an X-ray crystal structure of the dimeric PSP-1-Cu I complex, which revealed only two fused 5-membered chelate rings per Cu(I) center as opposed to the triple ring fusion that would be expected in a C 3 -symmetric 1:1 Cu(I) complex.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations